2017
DOI: 10.3390/toxins9080252
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Letibotulinum Toxin A for the Treatment of Dynamic Equinus Foot Deformity in Children with Cerebral Palsy: A Randomized Controlled Trial

Abstract: The objective of this clinical trial was to compare the efficacy and safety of letibotulinum toxin A and onabotulinum toxin A for improving dynamic equinus foot deformity in children with cerebral palsy (CP). In total, 144 children with spastic CP who had dynamic equinus foot deformity were assigned randomly to the Botulax group (injection of letibotulinum toxin A) or the Botox group (injection of onabotulinum toxin A). The Physician’s Rating Scale (PRS), ankle plantar flexor spasticity using the Modified Tard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…The changes in motor function, as assessed by GMFM-66 scores over time, were consistent with those of previous studies of BoNT-A for LL spasticity [ 56 , 57 , 58 ]. Although GMFM-66 improvements should be considered in the context of the patient’s global rehabilitation plan and cannot be solely attributed to incobotulinumtoxinA treatment, improvements after a single injection in the current study were within changes being reported as minimum clinically important differences by Oeffinger et al [ 59 ], who defined medium and large effects as changes of 0.7–1.7 and 1.2–2.7, respectively, in ambulatory children with CP.…”
Section: Discussionsupporting
confidence: 89%
“…The changes in motor function, as assessed by GMFM-66 scores over time, were consistent with those of previous studies of BoNT-A for LL spasticity [ 56 , 57 , 58 ]. Although GMFM-66 improvements should be considered in the context of the patient’s global rehabilitation plan and cannot be solely attributed to incobotulinumtoxinA treatment, improvements after a single injection in the current study were within changes being reported as minimum clinically important differences by Oeffinger et al [ 59 ], who defined medium and large effects as changes of 0.7–1.7 and 1.2–2.7, respectively, in ambulatory children with CP.…”
Section: Discussionsupporting
confidence: 89%
“…2,3,6 The observed distribution of ambulatory disabilities/independence in this study also resembles realworld clinical practice. 6,7,20 Prior clinical research has frequently focused on BoNT treatment in patients with lower GMFCS levels, with most studies having investigated the safety and efficacy of BoNT largely in ambulant participants, 8,9,[33][34][35] or in children with GMFCS levels of I to IV. 31 However, patients with GMFCS IV-V accounted for ~30% of the XARA study population and results showed notable efficacy and safety, with a reduced maximum total body dose for GMFCS IV-V in line with best practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because of the 6-month observation duration, some data were missing due to the level of patients’ compliance. However, data in this study were from a multicenter, double-blind, randomized, prospective clinical trial, and the observation period for 144 spastic CP children was 6 months [ 32 ]. The study provides evidence about the factors affecting outcomes, observational gait scores, and gross motor function after BoNT intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, double-blinded, randomized, prospective phase III clinical trial ( n = 144, 92 boys) of BoNT for the treatment of dynamic equinus in children with CP was undertaken recently with the primary intention of comparing the efficacy of letibotulinumtoxin A (Botulax; Hugel, Chuncheon, South Korea) and onabotulinumtoxin A (Botox; Allergan, Irvine, CA, USA). The study found injection of letibotulinum toxin A to be as effective and safe as that of onabotulinum toxin A for the treatment of dynamic equinus foot deformity in children with spastic CP (co-submitted) [ 32 ]. Secondary analyses of data from those patients who completed the trial were performed to evaluate the factors that affect the efficacy of BoNT for dynamic equinus in children with CP.…”
Section: Introductionmentioning
confidence: 99%